Suriname : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Suriname during 1994-96. In 1995, there was a major turnaround in Suriname's economic and financial situation following the expansionary fiscal and monetary policies pursued in the first half of the 1990s and the political and economic disruptions of the 1980s. The marked improvement was owing to the restoration of financial discipline, a strengthening of international bauxite prices, and the unification and subsequent stabilization of the exchange rate. The inflation fell further to less than 1 percent in 1996.